Sports Journalism Content When No Sports Occur: Framing Athletics Amidst the COVID-19 International Pandemic. (June 2022) - Sadri, Sean R.; Buzzelli, Nicholas R.; Gentile, Patrick; Billings, Andrew C.
On March 11, 2020, the National Basketball Association suspended its season after a player tested positive for COVID-19. Within days, the rest of the sports world similarly suspended play in the wake of the pandemic. This study focuses on sports media storytelling when covering athletic competition was no longer an option. Utilizing four distinct time periods and framing theory as the foundation of our theoretical framework, the content analysis examined shifts from the normal reporting routine and how those shifts morphed as pandemic information dictated. As the pandemic grew more widespread, health and safety became the predominant focus of national sports media. In spring 2020, sports news experienced a significant shift in coverage as economic and fairness frames were replaced with health, safety, and quality of life as the principal frames in the coded articles. By pinpointing the major differences in coverage across time, the study revealed that sports content and frames quickly shifted to reflect the perceived severity to the global health community, while the sources used in those articles stayed largely the same. The theoretical and applied implications of the study are discussed.